Advantages of the partial oral anastomosis, in those gastrectomized by ulcus type Billroth 11 - Matteucci, Pablo (Cirugía del Uruguay, 1974)
This paper is a contínuation of a previous statistical study and lists the várious advantages of partíal oral anastomosis as compared to total oral anastomosis in Billroth II type ulcus. A series of physiopathological hypothesis are put forth.